2015
DOI: 10.2174/1567205012666150701103107
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Alzheimer’s Disease: Integrated Molecular, Physiological, Anatomical, Biomarker, and Cognitive Dimensions

Abstract: Background: Alzheimer’s disease (AD), the most common form of dementia, is a progressive neurodegenerative disorder with interrelated molecular, physiological, anatomical, biomarker, and cognitive dimensions. Methods: This article reviews the biological changes (genetic, molecular, and cellular) underlying AD and their correlation with the clinical syndrome. Results: Dementia associated with AD is related to the aberrant production, processing, and clearance of beta-amyloid and tau. Beta-amyloid deposition in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(106 citation statements)
references
References 101 publications
4
102
0
Order By: Relevance
“…One useful source of information for early AD diagnosis is structural MRI, which can reveal abnormalities in a wide range of brain areas. Multiple studies have found structural MRI (sMRI), a useful diagnostic tool that can contribute to detecting AD-related modifications before the development of clinical symptoms (Raskin et al 2015;Xie et al 2015;Teipel et al 2015;Besson et al 2015;Goveas et al 2015). A different way in which sMRI can assist in early AD diagnosis is by providing data sets for a distinct group of recently developed analytical procedures involving advanced mathematical and statistical methods such as machine learning (Gorji and Haddadnia 2015;Klöppel et al 2008;Salvatore et al 2015;Zhan et al 2015) and graph theory, the formal study of networks (Supekar et al 2008;Stam et al 2009;He et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One useful source of information for early AD diagnosis is structural MRI, which can reveal abnormalities in a wide range of brain areas. Multiple studies have found structural MRI (sMRI), a useful diagnostic tool that can contribute to detecting AD-related modifications before the development of clinical symptoms (Raskin et al 2015;Xie et al 2015;Teipel et al 2015;Besson et al 2015;Goveas et al 2015). A different way in which sMRI can assist in early AD diagnosis is by providing data sets for a distinct group of recently developed analytical procedures involving advanced mathematical and statistical methods such as machine learning (Gorji and Haddadnia 2015;Klöppel et al 2008;Salvatore et al 2015;Zhan et al 2015) and graph theory, the formal study of networks (Supekar et al 2008;Stam et al 2009;He et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the case of [ tangles are sparsely detectable in the hippocampus (Raskin et al, 2015). Other studies also suggested that GPCR function is altered during AD (Thathiah and De Strooper 2011), especially in the CA1…”
Section: Discussionmentioning
confidence: 97%
“…In addition to these protein aggregates, the progressive loss of neurons and multiple neurotransmitter systems impairment represent the pathological hallmark of Alzheimer's disease (Tampellini, 2015;Raskin et al, 2015). Although the loss of cholinergic fibers seems to be closely related to cognitive impairment, perturbations of other neurotransmitter systems may be involved in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The neurobiology of AD is very complex, involving numerous pathological changes, while cholinergic dysfunction is just one of them. 33) Here we are considering that to develop new anti-dementia drugs in the future, aiming at the BDNF system may be more effective than the cholinergic system, as the former is more related to consolidation of memory compared with the latter. As we have known, by now a lot of compounds have been found to have anti-dementia effects in rodents via enhancing the BDNF signaling cascade, like arabinoxylan, WY14643, P7C3, and so on.…”
Section: Discussionmentioning
confidence: 99%